Dependence of the intermixing in InGaAs/InGaAsP quantum well on capping layers - Choi, WJ; Yi, HT; Lee, JI; Woo, DH (KOREAN PHYSICAL SOC, 2004)
The dependence of impurity-free vacancy disordering (IFVD) of InGaAs/InGaAsP quantum well (QW) structure with various semiconductor capping layers over the QW structure on the characteristics of the dielectric capping layer was studied by using SiO2 and SiNx film as capping layers. Thermal treatment of samples has shown that the amount of blue-shift depends not only on the dielectric capping material but also on the semiconductor capping material over the QW structure. It has been shown that a SiNx dielectric capping layer induces larger blue-shift of bandgap than a SiO2 capping layer for any semiconductor capping layer. For the semiconductor capping layer, it has been shown that an InP capping layer induced the largest blue-shift of bandgap and an InGaAs capping layer induced the smallest blue-shift of bandgap. The combination of dielectric-semiconductor capping condition has been proposed in order to obtain the largest differential bandgap shift spatially.
Keywords: MONOLITHIC INTEGRATION; LASER